2009
DOI: 10.1128/jvi.00832-08
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Independent Degradation of Hepatitis C Virus F Protein

Abstract: Hepatitis C virus (HCV) F protein is encoded by the ؉1 reading frame of the viral genome. It overlaps with the core protein coding sequence, and multiple mechanisms for its expression have been proposed. The full-length F protein that is synthesized by translational ribosomal frameshift at codons 9 to 11 of the core protein sequence is a labile protein. By using a combination of genetic, biochemical, and cell biological approaches, we demonstrate that this HCV F protein can bind to the proteasome subunit prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 63 publications
3
43
0
Order By: Relevance
“…The 20S proteasomes, on the contrary, degrade proteins and short peptides independently of ATP and ubiquitin. The list of proteins identified as substrates of 20S proteasomes extends every year; it includes, for example, proteins with a damaged tertiary structure [13] and some virus proteins [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The 20S proteasomes, on the contrary, degrade proteins and short peptides independently of ATP and ubiquitin. The list of proteins identified as substrates of 20S proteasomes extends every year; it includes, for example, proteins with a damaged tertiary structure [13] and some virus proteins [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…3). Such substrates include ornithine decarboxylase (ODC) 3 (4 -6), c-Fos (7,8), p21 Cip1 (9, 10), hepatitis virus F protein (11), and c-Jun (12), among others. Although the number of substrates identified as degraded by a ubiquitin-independent mechanism remains small, recent biochemical analyses indicate that the process may be more widespread than previously thought and contributes significantly to the regulation of protein turnover (13).…”
mentioning
confidence: 99%
“…For ubiquitin-dependent degrons, the recognition/binding phase is accomplished by covalently attached polyubiquitin moieties that recognize one or more subunits of the proteasomal complex (46,47). For ubiquitin-independent degradation, mechanisms that directly involve the target substrate's polypeptide chain are utilized (12,18,44). The initiation phase involves unfolding of the proteasome-bound substrate, "threading" of the substrate through the pore that leads to the proteolytic chamber, and entry into the chamber itself, where proteolysis ensues (11,38,46).…”
Section: Discussionmentioning
confidence: 99%
“…Waf1/Cip1 (16,17), the F protein of hepatitis C virus (18), and the NFB inhibitor IB␣ (19,20). Recent proteomic studies have indicated that as many as 20% of cellular proteins may be degraded in the absence of a requirement for ubiquitin modification (21), suggesting that many more ubiquitin-independent substrates remain to be discovered.…”
mentioning
confidence: 99%